Analysis of Bad Debt Resolution in Sharia Savings and Loans Cooperatives and Financing Using the Vosviewer Visualization Approach - Siti Nur Halizah; Taufiqur Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze and demonstrate in detail the process of systematic analysis of bibliographic data using VOSViewer with a literature review study. A detailed analysis process was prepared so that new users can more easily access and utilize VOSViewer. This research provides an evaluation of the information on non-performing loans and their development over ten years (2014-2024) using the mapping tools provided by VOSViewer. The aim is to show how efficient bibliometric analysis is by utilizing network visualization of predefined subjects with a mixed approach. In the data search, 200 relevant journals published between 2019-2024 were found, which were further grouped into 10 categories based on the year of publication. After clustering the journal data, the authors observed that the highest number of publications occurred in 2020-2021. There are many opportunities to explore new things in this topic. Furthermore, it is hoped that this research can be a reference for the author in conducting research and looking for further research topics.